Synergistic Effects of Cryptotanshinone and Senkyunolide I in Guanxinning Tablet Against Endogenous Thrombus Formation in Zebrafish - Li, Jun; Liu, Hao; Yang, Zhenzhong; Yu, Qingqing; Zhao, Lu; Wang, Yi (Frontiers in Pharmacology, 2021)
Thrombosis is a key pathological event in cardiovascular diseases, and is also the most important targeting process for their clinical management. New drug development in thrombosis treatment is still in great demand. According to the traditional Chinese medicine (TCM) theory, thrombosis belongs to the syndrome of blood stasis. Salvia miltiorrhiza Bunge and Ligusticum striatum DC. are two common TCM herbs with long-term documented function in promoting blood circulation and inhibiting thrombosis, especially when used together. Guanxinning Tablet, a modern Chinese drug which contains extracts of the two herbs, also showed strong therapeutic effects in coronary heart disease. However, the pharmacological mechanism is still lacking for the compatibility of the two herbs. Here, through zebrafish-based in vivo fluorescence screening, we demonstrated the synergistic effects between Salvia miltiorrhiza Bunge and Ligusticum striatum DC. in regulating endogenous thrombosis. Moreover, combined with high-resolution mass spectrometry, the main compounds of the botanical drugs were analyzed and screened in our model system. Interestingly, cryptotanshinone and senkyunolide I, two representative compounds respectively derived from the two herbs, also showed synergistic antithrombotic effects. Further analysis suggested that they may regulate thrombi formation at different levels via multiple signaling pathways, including oxidative stress, platelet activation and coagulation cascade. Taken together, our findings provided solid biological supports towards the drug compatibility theory of TCM, and suggested cryptotanshinone and senkyunolide I as promising drug candidates in thrombosis management.